Acts of Aesthetics: Publishing as Recursive Agency in the Long Eighteenth Century - Algee-Hewitt, Mark (Romanticism and Victorianism on the Net, 2010)
Of primary concern to late eighteenth-century society was the sheer volume of printed work being produced in England. The response of authors troubled by this perceived crisis was an outpouring of works on taste, aesthetics, genre and literature, which attempted to describe and provide corrective solutions to the problem of over-publication. Yet this response itself, of course, only added to the number of works within Britain. How did the solution to a deluge of print become more printed materials? Did these authors envision print’s agency as a self-corrective process? And, if so, how can we recover and perhaps even model the connections between works that encompassed the responses to print? This essay outlines a potential solution to this problem by sampling a highly focused selection of digitized texts that raise the issue of over-publication. Through a quantitative analysis of these texts, it identifies the lexical patterns that may reveal the ways in which authors of the period envisioned the work of aesthetics. In particular, this article identifies an emerging consensus on how printed objects became agents within the socio-cultural world of the long eighteenth century: both as objects which could act on readers and as objects which could act on other printed texts. By comparing the language that these clusters of texts deploy to discuss the agency of print to their traditional generic, theoretical or historical groupings, we can begin to examine the process by which the potential power of print became the solution to the dangers it, itself, presented.